ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP PENETAPAN UNDANG UNDANG CIPTA KERJA TAHUN 2020 - Francisca Kristiastuti; Utari Kartika Sari (Business Administration Department - Universitas Katolik Parahyangan, 2021)
The 2020 Job Creation Law of Indonesia (Ciptaker), which was passed on October 5, 2020, is considered to have a positive impact on the Indonesian capital market. The insights in the stipulation of the Job Creation Act are well utilized by investors in making investment decisions. This research aims to analyze the reaction of the Indonesian capital market by observing the movement of stock prices and stock trading volume. The movement of stock prices is used to examine whether there is an abnormal return, while the trading volume is used to see whether there is an increase in trading volume activity. This research uses an event study method with an observation period of 21 days consisting of 10 days before and 10 days after the announcement of the 2020 Job Creation Act stipulation. The sample consists of 14 manufacturing companies whose shares are listed in the LQ 45 Index with certain criteria. The results show that there was no difference in the average abnormal return between before and after the announcement of the 2020 Job Creation Act stipulation. However, there was a difference in the average trading volume activity before and after the 2020 Job Creation Act announcement.